Avaliação do desempenho de métodos de estimativa da evapotranspiração de referência para o município de Maués, Amazonas - Barbosa, João Victor Góes (Brasil, 2021)
Accurate estimation of reference evapotranspiration is essential for calculating crop water requirements, irrigation scheduling and water resource management. In this sense, the objective of this work was to evaluate the performance of the Blaney-Criddle, Hargreaves, Jensen-Haise and Camargo methods in relation to the Penman-Monteith-FAO method, to estimate the reference potential evapotranspiration in the city of Maués - AM, based on data provided by the National Institute of Meteorology, from an automatic station, series 2009-2018. From the atmospheric variables: pluviometric precipitation, dry bulb temperature, wet bulb temperature, maximum temperature, minimum temperature, relative humidity, wind speed, atmospheric pressure, global solar radiation and daily total insolation, the daily reference evapotranspiration was estimated by the methods of Penman-Monteith, Blaney-Criddle, Hargreaves, Camargo and Jensen-Haise. To compare the reference evapotranspiration estimation methods, the standard error of estimate was used in relation to the standard method, correlation coefficient, determination coefficient, agreement index and performance coefficient. Among the results obtained, it was found that all evaluated methods overestimated the reference evapotranspiration compared to the standard method, Penman-Monteith, in all months of the year, and the Blaney-Criddle, Hargreaves and Jensen-Haise methods showed performance "great” while Camargo presented a “very good” performance. The Blaney-Criddle, Hargreaves, Jensen-Haise and Camargo methods satisfactorily met the reference evapotranspiration estimate for Maués-AM, and can be used to replace the standard Penman-Monteith FAO-56 method when all variables are not available for the estimate of reference evapotranspiration.